Вплив COVID-19 на ринок вантажних залізничних перевезень - Двуліт, З. П.; Мельник, О. Г.; Данилюк, І. А.; Dvulit, Z. P.; Melnyk, O. G.; Danyliuk, I. A. (Видавництво Львівської політехніки, 2020)
Розглянуто проблему впливу пандемії, спричиненої СOVID-19 на ринок вантажних залізничних перевезень. Проаналізовано за показниками обсягів перевезень та вантажообігу: діяльність всіх видів транспорту, залізниць України впродовж січня-липня 2019– 2020 рр.; їх структуру за напрямами (транзитні, імпортні, експортні, внутрішні) за I півріччя 2019–2020 рр. Виокремлено фактори впливу на стан та зміну цих показників для АТ “Укрзалізниця”. Запропоновано заходи щодо зменшення негативного впливу різних факторів на стан та розвиток ринку вантажних залізничних перевезень.

The COVID-19 pandemic has changed not only the lives of many people, but also the situation in global and local markets. Worldwide, there has been a significant reduction in production capacity due to the closure of borders between countries and the introduction of self-isolation. The spread of the epidemic disrupted the usual trade relations between producers and consumers, caused serious changes in the activities of logistics companies. The crisis caused an imbalance of freight flows due to changes in demand, cessation of production activities and restrictions: there was a decrease in freight traffic worldwide and locally due to the closure of borders, mass closures, rising dollar, isolation, decline demand and purchasing power, as well as the state of fear and uncertainty among consumers. Many factories and plants around the world were quarantined, leaving nothing and no one to transport; lack of simple, clear rules of the game in the conditions of quarantine for representatives of the logistics market, etc. Quarantine measures taken to reduce the spread of morbidity caused by COVID-19 have significantly affected Ukraine’s transport system, including the rail freight market. The article considers the problem of the impact of the pandemic caused by COVID-19 on the freight rail market. As a result, we analyzed the indicators of traffic by various modes of transport and freight turnover for January-July 2019–2020; monthly dynamics of freight traffic by railways of Ukraine cumulatively during January-July 2019–2020; structure of distribution of cargo turnover and transportation by directions (transit, import, export, domestic transportation) for the first half of 2019- 2020. Factors influencing the state and change of volumes and structure of freight transportation of JSC “Ukrzaliznytsia” are singled out. Measures to reduce the negative impact of various factors on the state and development of the rail freight market are proposed. Analyzed in this article, the work of domestic and foreign scientists, managers, made it possible to identify the features of successful and unsuccessful public management of transport infrastructure around the world during the pandemic in the field of rail freight. It should be noted that countries have made decisions to combat the spread of the disease, to support the production and economic activities of economic entities in different ways. Decisions made at different levels of government, as time has shown, were not always be timely, effective and reasonable. The coronavirus pandemic has been a challenge for the global transport system. At the same time, it showed its critical impact on both the functioning of the economy and the quality of life of the population.
Impact of Covid-19 on rail freight market
Keywords: управління; вантажні перевезення; залізниці; міжнародні перевезення; вантажообіг; COVID-19; АТ “Укрзалізниця”; фактори впливу; management; freight transportation; railways; international transportation; freight turnover; COVID-19; JSC “Ukrzaliznytsia”; factors of influence; 616-036.21; 656.073